Emotional outcomes of Ugandan SME buyer-supplier contractual conflicts - Mpeera Ntayi, Joseph (International Journal of Social Economics, 2012)
The purpose of this paper is to provide a multilevel investigation of the existence and relationship between severity of buyer-supplier contractual conflicts, emotional outcomes and disengagement behaviour arising out of the contractual disputes in Ugandan small to medium-sized enterprises (SMEs). Design/methodology/approach – This paper undertakes a large-scale comprehensive survey covering 839 SMEs’ buyers together with their corresponding suppliers using Krejcie and Morgan sample size determination criteria. Respondents were managers selected on the basis of their purchasing experience and knowledge of the subject matter under investigation. Data were subjected to a confirmatory factor analysis as a quasi-judicial analytical approach to assess the goodness-of-fit of the latent structure underlying the constructs under investigation. Findings – The results demonstrate that both the confirmatory factor analysis and the structural equation model have a good fit. The direct effects of the severity of buyer-supplier conflicts and emotional outcomes of buyer-supplier emotions taken together is significant and explains 37 per cent of the variance in buyer-supplier disengagement. Originality/value – The study predicts the emotional outcomes of buyer-supplier conflicts which were thought to be idiosyncratic, and erratic. Their connection to organizational outcomes was considered convoluted.
Keywords: Uganda; Small to medium-sized enterprises; Contracts; Disputes; Conflict; Emotions; Buyer-supplier; Disengagement